2021
DOI: 10.1073/pnas.2110807118
|View full text |Cite
|
Sign up to set email alerts
|

Steady agronomic and genetic interventions are essential for sustaining productivity in intensive rice cropping

Abstract: Intensive systems with two or three rice (Oryza sativa L.) crops per year account for about 50% of the harvested area for irrigated rice in Asia. Any reduction in productivity or sustainability of these systems has serious implications for global food security. Rice yield trends in the world’s longest-running long-term continuous cropping experiment (LTCCE) were evaluated to investigate consequences of intensive cropping and to draw lessons for sustaining production in Asia. Annual production was sustained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Rice plays a major role in achieving global food security but the crop now is under several threats, including yield stagnation in major rice-producing regions, negative environmental impacts of the overuse of irrigation water and agrochemicals, high labour requirements which is under short supply, and increasing concerns of loss of natural habitats due to intensive rice cultivation 1 3 . In particular, traditional puddled-transplanted rice (PTR) requires more irrigation water and labour than direct-seeded rice (DSR) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Rice plays a major role in achieving global food security but the crop now is under several threats, including yield stagnation in major rice-producing regions, negative environmental impacts of the overuse of irrigation water and agrochemicals, high labour requirements which is under short supply, and increasing concerns of loss of natural habitats due to intensive rice cultivation 1 3 . In particular, traditional puddled-transplanted rice (PTR) requires more irrigation water and labour than direct-seeded rice (DSR) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Shen Yuan 1 , Alexander M. Stuart 2 , Alice G. Laborte 2 , Juan I. Rattalino Edreira 3 , Achim Dobermann 4 , Le Vu Ngoc Kien 5 , Lưu Thị Thúy 6 , Kritkamol Paothong 7 , Prachya Traesang 8 , Khin Myo Tint 9 , Su Su San 10 , Marcelino Q. Villafuerte II 11 , Emma D. Quicho 2 , Anny Ruth P. Pame 2 , Rathmuny Then 12 , Rica Joy Flor 12 , Neak Thon 13 , Fahmuddin Agus 14 , Nurwulan Agustiani 15 , Nanyan Deng 1 , Tao Li 16 and Patricio Grassini 3 ✉ Southeast Asia is a major rice-producing region with a high level of internal consumption and accounting for 40% of global rice exports. Limited land resources, climate change and yield stagnation during recent years have once again raised concerns about the capacity of the region to remain as a large net exporter.…”
Section: Southeast Asia Must Narrow Down the Yield Gap To Continue To...mentioning
confidence: 99%
“…Although it has been demonstrated that rice yields can be maintained in such intensive monoculture systems, it has also proven to be very difficult to raise them further, even with the best available varieties and technologies 14 .…”
mentioning
confidence: 99%
“…In all, rice production is predicted to require an increase of 117% by 2050 to offset these various pressures (Ray et al 2013). Current trends in productivity due to breeding are 1% or less (Ladha et al 2021;Khanna et al 2022), far short of the 2.4% predicted to be required to meet these demands.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many initiatives have increased genetic gains to 2.4% or higher (Ladha et al 2021;Nayak et al 2022). These initiatives emphasize mechanisms to reduce the breeding cycle time, increase selection accuracy, increase selection intensity, etc.…”
Section: Introductionmentioning
confidence: 99%